2014
DOI: 10.1016/j.mayocp.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Aortic Valve Replacement for Severe Aortic Stenosis in the Transcatheter Valve Era

Abstract: Surgical aortic valve replacement had been the only definitive treatment of severe aortic stenosis before the availability of transcatheter valve technology. Historically, many patients with severe aortic stenosis had not been offered surgery, largely related to professional and patient perception regarding the risks of operation relative to anticipated benefits. Such patients have been labeled as "high risk" or "inoperable" with respect to their suitability for surgery. The availability of transcatheter aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…The risk calculator uses well defined covariates to estimate operative risk. With the advent of transcatheter valve insertion, the precision of the STS predicted risk of mortality has come under examination as other non‐database covariates are being recognized to affect operative risk . One example of such a non‐database covariate is frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The risk calculator uses well defined covariates to estimate operative risk. With the advent of transcatheter valve insertion, the precision of the STS predicted risk of mortality has come under examination as other non‐database covariates are being recognized to affect operative risk . One example of such a non‐database covariate is frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated associations of frailty with dysregulation of the immune, hormonal, and endocrine systems including up-regulation of inflammatory cytokines, decreased testosterone levels, and glucose intolerance due to insulin resistance, leading to physical inactivity, malnutrition, and sarcopenia (a state of progressive decline in muscle mass and strength) (16,19). The presence of frailty has been associated with many adverse outcomes including an increased risk of falls, disability, institutionalization, health care resource use as well as mortality (8,(20)(21)(22)(23).…”
Section: Adverse Effects Of Frailtymentioning
confidence: 99%
“…This syndrome is very prevalent is reported in up to 80% of patients undergoing TAVR (5)(6)(7). Previous studies have demonstrated the adverse effects of frailty on outcomes including disability, dependency, falls, the need for long-term care facility and mortality after cardiac surgery and procedures, such as coronary artery bypass grafting, valve repair or replacement, TAVR, or combined procedures (4,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios realizados en subpoblaciones mayores de 80 años con EA severa sintomática han demostrado que la sustitución valvular reduce la mortalidad al año y a los 5 años a 13% y 32% respectivamente 7 . Sin embargo solo entre el 50% y el 70% de los pacientes se llegan a operar, debido a que una parte importante de esta población es de edad avanzada y tiene múltiples comorbilidades, que hacen que se desestimen para cirugía convencional por su elevado riesgo quirúrgico [8][9][10] . El diagnóstico de la EA es sencillo con una adecuada anamnesis y exploración física sistmática.…”
Section: Introductionunclassified